2005
DOI: 10.1021/cm048255p
|View full text |Cite
|
Sign up to set email alerts
|

New Borate Precursors for Boron Nitride Powder Synthesis

Abstract: The thermal decomposition of guanidinium tetraborate, pentaborate, and nonaborate has been characterized under nitrogen and ammonia atmospheres, and conditions have been defined for bulk powder and aqueous aerosol transformations of these precursors to boron nitride (BN). The bulk pyrolyses under ammonia (600-1400 °C) produce micrometer-and sub-micrometer-sized platelet morphology particles with oxygen contents of 3-18 wt. %. Subsequent pyrolysis of these powders at 1600 °C under NH 3 reduces the oxygen conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 21 publications
(27 reference statements)
4
32
0
Order By: Relevance
“…. The detailed spectrum analysis of MB and GB was made in the previous studies, and the results were in accordance with these studies …”
Section: Methodssupporting
confidence: 75%
“…. The detailed spectrum analysis of MB and GB was made in the previous studies, and the results were in accordance with these studies …”
Section: Methodssupporting
confidence: 75%
“…The calculated TG curves are obtained on the basis of common additive rules. As already demonstrated in the literature [23,24], the degradation of GB (Fig. 2) and IB (Fig.…”
Section: Resultssupporting
confidence: 82%
“…3) occurs in two steps in nitrogen via dehydration (first step) and the degradation of amine moiety (second step). The detailed analysis carried out by Schubert et al [23] and Wood et al [24] showed that the gaseous products of water, CO 2 , and NH 3 are formed during the degradation of both boron compounds. Also in our case, the same mechanism has been observed, and at the end of the test at 1,073 K, GB and IB retain 46 and 58 % of their mass, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations